The Weathering Microbiome of an Outcropping Granodiorite - Napieralski, Stephanie A.; Roden, Eric E. (Frontiers in Microbiology, 2020)
Microorganisms have long been recognized for their capacity to catalyze the weathering of silicate minerals. While the vast majority of studies on microbially-mediated silicate weathering focus on organotrophic metabolism linked to nutrient acquisition, it has been recently demonstrated that chemolithotrophic ferrous iron [Fe(II)] oxidizing bacteria (FeOB) are capable of coupling the oxidation of silicate mineral Fe(II) to metabolic energy generation and cellular growth. In natural systems, complex microbial consortia with diverse metabolic capabilities can exist and interact to influence the biogeochemical cycling of essential elements, including iron. Here we combine microbiological and metagenomic analyses to investigate the potential interactions among metabolically diverse microorganisms in the near surface weathering of an outcrop of the Rio Blanco Quartz Diorite (DIO) in the Luquillo Mountains of Puerto Rico. Laboratory based incubations utilizing ground DIO as metabolic energy source for chemolithotrophic FeOB confirmed the ability of FeOB to grow via the oxidation of silicate-bound Fe(II). Dramatically accelerated rates of Fe(II)-oxidation were associated with an enrichment in microorganisms with the genetic capacity for iron oxidizing extracellular electron transfer (EET) pathways. Microbially oxidized DIO displayed an enhanced susceptibility to the weathering activity of heterotrophic microorganisms compared to unoxidized mineral suspensions. Our results suggest that chemolithotrophic and organotrophic microorganisms are likely to coexist and contribute synergistically to the overall weathering of the in-situ bedrock outcrop.